The genus Leucophenga (Diptera, Drosophilidae), part III: the interrupta species group from the Oriental region, with morphological and molecular evidence - Huang, Jia; Li, Tong; Chen, Hongwei (Zootaxa, 2013)
A new species group, the interrupta group, is established within the genus Leucophenga based on two known and three new species, all of which are endemic to the Oriental region: L. interrupta Duda, 1924, L. neointerrupta Fartyal & Toda, 2005, L. bifurcata sp. nov., L. quadrifurcata sp. nov. and L. retifoliacea sp. nov. A key to the five species of the interrupta group is provided. Sixteen mtDNA COI sequences of the five species are analyzed; the molecular data are used as complementary evidence for the species boundaries defined by the morphological data.